Delaying the Employer Mandate Small Change in the Short Term, Big Cost in the Long Run - Price, Carter C. (RAND Corporation, 2013)
In July 2013, the Obama administration announced a one-year delay in enforcement of the Affordable Care Act's penalty on large employers that do not offer affordable health insurance coverage. To help policymakers understand the implications of this decision, RAND analysts employed the COMPARE microsimulation model to gauge the impact of the one-year delay of the so-called employer mandate.